PENGARUH PERAN GURU TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SD YPK SILO DOREHKAR KABUPATEN RAJA AMPAT - Renai Susance Mambrisauw; Anis Alfian Fitriani; Asrul (JIP: Jurnal Ilmu Pendidikan, 2026)
This study is motivated by the low initial reading skills of first-grade students at SD YPK Silo Dorehkar, Raja Ampat Regency, which is a critical issue for successful learning. The main objective is to examine the influence of teachers’ roles on students' initial reading skills. A quantitative method with a quasi-experimental one-shot case study design was employed involving 36 students as the sample. Data were collected through questionnaires and reading skill tests, then analyzed using validity, reliability, normality, linearity tests, and simple linear regression. The results revealed that the teachers’ roles were categorized as very strong with an average score of 65.8, while students’ initial reading skills were very good with an average score of 27.4. Regression analysis showed a positive and significant influence of teachers’ roles on initial reading skills with a determination coefficient of 64.3% (p < 0.05). In conclusion, teachers’ roles significantly contribute to enhancing students’ initial reading skills in this remote area, offering important implications for the development of theory and practice in elementary reading instruction. The study recommends optimizing teachers’ roles and improving the learning environment for maximal outcomes.